2021
DOI: 10.3390/molecules26195876
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Catalytic Reduction of 4-Nitrophenol Using Copper(II) Complexes with N,O-Chelating Schiff Base Ligands

Abstract: The reduction of 4-nitrophenol to 4-aminophenol by sodium borohydride was used as a model to test the catalytic activity of copper(II) complexes containing N,O-chelating Schiff base ligands. In this study, a series of copper(II) complexes containing respective Schiff base ligands, N′-salicylidene-2-aminophenol (1), N′-salicylidene-2-aminothiazole (2), and N,N′-bis(salicylidene)-o-phenylenediamine (3), were synthesized and characterized by elemental analysis, Fourier transform infrared (FT-IR), and UV-Visible (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Upon the cata'yst's addition, hydrazine hydrate and 4-NP were adsorbed on its surface and catalytic reduction was initiated immediately by transferring the hydride from the hydrazine hydrate donor to the acceptor 4-NP. Finally, with the elimination of a molecule of H2O, 4-AP departed the catalyst's surface [82]. The recyclability of the prepared catalyst was carried out five times by washing it multiple times with deionized water and reusing it for another cycle under the optimum conditions.…”
Section: Catalytic Reduction Of 4-npmentioning
confidence: 99%
“…Upon the cata'yst's addition, hydrazine hydrate and 4-NP were adsorbed on its surface and catalytic reduction was initiated immediately by transferring the hydride from the hydrazine hydrate donor to the acceptor 4-NP. Finally, with the elimination of a molecule of H2O, 4-AP departed the catalyst's surface [82]. The recyclability of the prepared catalyst was carried out five times by washing it multiple times with deionized water and reusing it for another cycle under the optimum conditions.…”
Section: Catalytic Reduction Of 4-npmentioning
confidence: 99%
“…A broadband (3200-3550 cm -1 ) is present in all of the complexes, showing the presence of water molecules. Table (5) and Figures (7)(8)(9)(10) offer the ligands' UV-Visible spectral data and their complexes. At 225 nm and 246 nm, the aromatic band about the ligands L 1 and L 2 , respectively, was seen to attribute to the vanillin π π* transition's phenyl.…”
Section: Ir and Uv Spectra Of Ligands And Complexesmentioning
confidence: 99%
“…They are considered significant for a wide variety of progress metal catalysis responses, including epoxidation of ole-fins 5 , lactide polymerisation 6 , and the opening of the asymmetric rings of epoxides 7 . The chelating Schiff base ligands derived based on different carbonyl compounds, and diamines include a highly notable class of compounds with numerous applications in synthetic 8 , catalytic clinical 9 , analytical 10 , and biochemical 11 processes. Previous studies have shown that enhancement of the coordinating potential of diamine compounds like meta phenylene diamine happens when they are condensed with different carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[53,54] These posed to the diffusion-controlled mechanism, which is associated with the presence of Cts features, forming layers and capping the surfaces of synthesized Cu-NPs. [55,56] The limited flexibility of Cts, [52] which caps and stabilizes Cu-NPs, restricts 4-NP diffusion onto the NP surface. This constraint, caused by the Cts layer, reduces the exposed surface area of the particles available for reacting with borohydride ions.…”
Section: Heterogeneous Catalysis Of Copper Nanoparticles In 4-nitroph...mentioning
confidence: 99%